Virtual coach strength training can "improve the physical health of the elderly through an experimental study - Kuswahyudi, kuswahyudi; Setiakarnawijaya, Yasep (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
Abstract: Decline in physical condition in the elderly is a significant health challenge, especially related to muscle strength, mobility, and quality of life. This study aims to evaluate the effectiveness of Virtual Coach Strength Training in improving the physical health of the elderly through an experimental study approach. The research method used was a quasi-experimental experiment with a pre-test and post-test control group design. The sample consisted of 30 elderly people aged 60–75 years, who were divided into two groups: an experimental group that followed a virtual coach-based strength training for 8 weeks, and a control group that did not receive intervention. The measurement instruments include the Senior Fitness Test (SFT) to assess muscle strength, flexibility, balance, and cardiorespiratory fitness. The results of statistical tests showed a significant improvement in the experimental group compared to the control group (p < 0.05), especially in the aspect of leg and upper body strength. These findings suggest that virtual coach-based strength training can be an effective strategy to improve the physical health of the elderly. This study recommends the use of technology in elderly fitness interventions as an innovative and adaptive approach.